INTERNET OF THINGS SOIL MOISTURE TESTING AND MONITORING FOR EARTHING SYSTEM - HANAPI, MOHAMAD AMIRUL IEZHAM (2018)
Earthing system is very important in installation of electrical power distribution system. It secures human safety as well as provide protection to expensive and electrical equipments. The best earthing system has low resistance of the soil in order to transfer fault current faster. There are many factors that contribute to the low soil resistance which is moisture, temperature, acidity, types of soil, soil composition, pH value and other. In this project, soil moisture is the main concern in monitoring the earthing system. First of all, there are certain procedures to install the earthing system. An earth tester must be used to check the soil resistance before planting the 1500mm copper rod into the preferred area which the area that has very moist soil. After founding the preferred area for the earthing system or by using back-filled earthing system provided do not found the preferred area, the earthing system should be monitored by testing again the soil resistance using the earth tester for every two or three days depend on the weather condition either a rainy day or not. The earth tester must be set up for every two days for testing and monitoring because it does not have a feature that can send the soil resistance value to a base station or via internet to the person in charge for monitoring the earthing system.